Effects of chemical disorder in the itinerant antiferromagnet Ti1−xVxAu. (17th August 2018) - Huang, C-L; Santiago, J M; Svanidze, E; Besara, T; Siegrist, T; Morosan, E
Abstract: The fragile nature of itinerant magnetism can be exploited using non-thermal parameters to study quantum criticality. The recently discovered quantum critical point (QCP) in the Sc-doped (hole-like doping) itinerant antiferromagnet TiAu (Ti1− x Sc x Au) raised questions about the effects of the crystal and electronic structures on the overall magnetic behavior. In this study, doping with V (electron-like doping) in Ti1− x V x Au introduces chemical disorder which suppresses antiferromagnetic order from 36 K for x   =  0 down to 10 K for x   =  0.15, whereupon a solubility limit is reached. Signatures of non-Fermi-liquid behavior are observed in transport and specific heat measurements similar to Ti1− x Sc x Au, even though Ti1− x V x Au is far from a QCP for the accessible compositions .